1979
DOI: 10.1029/jb084ib06p02929
|View full text |Cite
|
Sign up to set email alerts
|

Properties and effects of dust particles suspended in the Martian atmosphere

Abstract: Direct measurements of the optical depth above the two Viking landers are reported for a period covering the summer, fall, and winter seasons in the northern hemisphere, a time period during which two global dust storms occurred. The optical depth had a value of about 1 just before the onset of each storm; it increased very rapidly, on a time scale of a few days, to peak values of about 3 and 6 with the arrival of the first and second storms, respectively; and it steadily decreased shortly thereafter (≳ few da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
328
6

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 523 publications
(352 citation statements)
references
References 33 publications
(49 reference statements)
18
328
6
Order By: Relevance
“…Additionally, the surface evolution of Mars is currently dominated by the atmospheric dust cycle, which governs the rate of exhumation, transportation, and deposition of dust on the surface [Christensen and Moore, 1992;Thomas and Gierasch, 1985]. Regional and global dust storms were originally assumed to dominate this cycle, but Pollack et al [1979] showed that dust settles from the atmosphere too rapidly after such events to account for the continuous opacity caused by suspended particles. Dust devils have been shown to help maintain this perennial atmospheric haze [Fisher et al, 2005], and are important mechanisms for redistributing substantial amounts of the Martian surface over short geological time periods [Ringrose et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the surface evolution of Mars is currently dominated by the atmospheric dust cycle, which governs the rate of exhumation, transportation, and deposition of dust on the surface [Christensen and Moore, 1992;Thomas and Gierasch, 1985]. Regional and global dust storms were originally assumed to dominate this cycle, but Pollack et al [1979] showed that dust settles from the atmosphere too rapidly after such events to account for the continuous opacity caused by suspended particles. Dust devils have been shown to help maintain this perennial atmospheric haze [Fisher et al, 2005], and are important mechanisms for redistributing substantial amounts of the Martian surface over short geological time periods [Ringrose et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…Sun at various zenith angles in the broadband solar channel centered on 670 nm [Pollack et al, , 1979Colburn et al, 1989]. These are shown in Plates la and ld.…”
Section: Both Landers Measured Optical Depth By Directly Imaging Thementioning
confidence: 99%
“…The current standard view of the dust cycle derives from Viking Lander (VL) measurements of the visible optical depth since the optical depth of the atmosphere provides a measure of the amount of suspended aerosols. The key assumption in the interpretation of these data has been that only dust significantly contributes to the daytime opacity [Pollack et al, 1979;Colburn et al, 1989] and hence that the amount of atmospheric dust can be directly derived from them. However, dust is not the only Copyright 2000 by the American Geophysical Union.…”
Section: Introductionmentioning
confidence: 99%
“…The lower portion of the mosaic, where the layered deposits appear, was corrected for atmospheric scattering (Plate 2) and used to create the R/V mosaic shown in Figure 2. The atmospheric brightness and attenuation at selected points in the mosaic were predicted using 2.5-tz radius particles [Pollack et al, 1979] with the scattering properties given in Table 2. The best fit model (normal optical depth = 0.13) was run at 35 points in a 400 x 400 pixel grid; then bilinear interpolation was used to approximate the atmospheric brightness and attenuation at every other pixel in each color mosaic.…”
Section: Processing and Mapping Methodsmentioning
confidence: 99%